Stoichiometry engineering of ternary oxide ultrathin films: BaxTi2O3 on Au(111) - Wu, C; Castell, M; Goniakowski, J; Noguera, C (American Physical Society, 2015)
Ternary oxide Bax Ti2 O3 ultrathin films on Au(111) substrates (x ≤ 2/3) have been studied using a joint experimental and theoretical approach, including the use of scanning tunneling microscopy (STM), first principles calculations, and Monte Carlo simulations. The films are created by first covering the Au(111) substrate with a Ti2 O3 (2×2) honeycomb (HC) network and then evaporating low concentrations of Ba atoms onto this film. STM imaging shows that the Ba atoms adsorb individually in the hollow sites of the HC network. Depending on the Ba coverage x, which ranges from 0 to 2/3, two ordered phases can be identified at x = 1/3 and x = 2/3. A disordered labyrinthlike phase is observed for values of x between 1/3 and 2/3. Theoretical modeling shows that the structural character of these films is driven by the charge transfer that occurs between the electropositive Ba atoms and the electronegative Ti2 O3/Au substrate. This results in a number of calculated effects including an increase in the film rumpling and a reduction of the film work function with increasing x. The evolution of the structure of the thin films as a function of Ba coverage can be described by a lattice gas model with first-, second-, and third-neighbor Ba-Ba repulsive interactions. The range of the dipolar interactions is a key factor in understanding the behavior of Ba ordering. The structural and electronic flexibility, which can be engineered through stoichiometry, temperature, or support control, makes these ultrathin films promising materials for applications related to adsorption or reactivity, or as template supports for the growth of size-selected clusters.